Allopurinol improves myocardial reperfusion injury in a xanthine oxidase-free model - Hopson, Steven B.; Lust, Robert M.; Sun, You Su; Zeri, Richard S.; Morrison, Ron F.; Otaki, Masaki; Chitwood, W. Randolph (East Carolina University, 1995)
The ability of allopurinol to protect against reperfusion injury in the heart has usually been attributed to its xanthine oxidase (XO)- inhibiting properties. Human myocardium how- ever, has exhibited low levels of XO activity. To investigate the effects of allopurinol in an XO-free model and determine whether pretreat- ment is necessary, 12 domestic pigs (15 kg to 20 kg) underwent occlusion of the left circum- flex for 8 minutes followed by reperfusion for 4 hours. One group received allopurinol infusion (5 mg/kg IV) at occlusion over 45 minutes and a control group (n = 6) received a saline infusion (same volume). Left ventricular and aortic pressure, electrocardiograms, and regional wall motion (sonomicrometry) were monitored throughout the process. Regional blood flow (microspheres) were obtained before, during, and 5, 10, and 30 minutes after ischemia. Occlusion decreased transmural flow at the midpapillary level by 75% (0.28 versus 1.10 mUminute/g). The allopurinol-treated group exhibited a mild, generalized hyperemia at 5 minutes (ischemic zone: 1.44 versus 1.10 mU min/g, which returned to control levels at 10 and 30 minutes. In contrast, the control group was associated with only 80% restoration of resting blood flow at 5 minutes (0.84 versus 1.10 mUmin/g), which stabilized at 63% of control levels at 10 and 30 minutes. When evaluated for the propensity of arrhythmias using an arbitrary arrhythmia score, the al- lopurinol group demonstrated no myocardial ectopy when compared with the focal ectopy routinely encountered in the control group at all time intervals. Since pigs have no detectable levels of XO activity, allopurinol must exert its protectant effect during myocardial reperfu- sion by an alternative mechanism. Because protection was evident without pretreatment, beneficial effects may not necessarily be the result of allopurinol degradation products; therefore, pretreatment with allopurinol may not be necessary. These results are clinically important when considering the use of allopuri- nol in an emergent coronary angioplasty or coronary artery bypass grafting. Originally published Journal of the National Medical Association, Vol. 87, No. 7, July 1995
Keywords: Pretreatment; Oxypurinol; Swine; Myocardial shortening; Microspheres